Iatrogenic Trauma to Gingiva – A Case Series - P.R, Ganesh (Biology, Engineering, Medicine and Science Reports)
Background: Iatrogenic trauma is any traumatic injury inflicted by intervention, therapy or activity by a healthcare professional. The aim of this article is to present a series of rare traumatic lesions of the gingiva of Iatrogenic etio-pathology. Methods: A total of nine cases of traumatic lesions of the gingiva due to ill-fitting orthodontic appliances or inappropriate orthodontic therapy are reported and their management by non-surgical periodontal therapy is discussed. Results: Orthodontic appliance therapy in addition to the effects on the periodontium has very rarely certain deleterious effects on the gingiva. The commonest of these manifestations is an inflammatory gingival enlargement. The management of these types of lesions involves elimination of the insult, motivation for personal oral hygiene maintenance, non surgical periodontal therapy and very rarely mucogingival surgery. Conclusion: Respect to the oral soft tissues, constant motivation of patients and adequate time spent on thorough examination during review visits prevent many Iatrogenic insults to the tissues. Any orthodontic therapy requires the participation of a consultant Periodontist to manage the soft tissue problems which might arise from appliance wear.
Keywords: Gingival injuries; Iatrogenic disease; Orthodontic Appliances; Adverse effects appliances; Non surgical periodontics